Exotic species of zooplankton in the Upper Paraná River floodplain, Daphnia lumholtzi Sars, 1885 (Crustacea: Branchiopoda) - Simões, Nadson Ressyé (2020)
The integrity of aquatic ecosystems is being challenged worldwide by invading species, which has been one of the frequent causes of biodiversity loss. The invader may cause extinctions of vulnerable native species through predation, grazing, competition and habitat alteration. Daphnia lumholtzi G. O. Sars, 1885, a native cladoceran from Australia, Southwestern Asia and North Africa, has recently been found in the Neotropical region. The D. lumholtzi records from the Upper Paraná River floodplain were restricted to the Pombas floodplain lake (22° 47' 55.92" S and 53° 21' 32.58" W) and Pau Véio Backwater (22° 44' 50.76" S and 53° 15' 11.16" W), in 2003 and 2008, respectively. This species can be distinguished from the other Daphnia species registered in Brazil by the conspicuous pointed fornix, the sizes of the tail spine and helmet, and a carapace ventral margin with strong spines. The high temperatures in the tropical region, as well as the increase in water transparency and the decrease in nutrient concentration observed in the environments of the Upper Paraná River floodplain due to the upstream retention by dams, may favor the development of D. lumholtzi populations. The development of populations of D. lumholtzi in natural environments of the Upper Paraná River floodplain may suggest that this species is establishing in the Neotropical region.